(untitled) (Scientific journal of the Fergana State University, 2024)
In the oldest Turkic written monuments, the morphological indicators of the quantity category, such as the suffixes “-an,” “-lar,” and “-lər,” appear in various forms in contemporary Turkic languages and in the dialects and accents of the Azerbaijani language. Among these suffixes, the plural morpheme “-ça” remains unchanged phonemically, while the suffixes “-lar” and “-lər” exhibit diverse phonetic forms due to the physiological acoustic nature of the consonant “l.” Variations in this morphological indicator are observed both in consonantal and vowel phonemes: -lar, -lər, -lar, -ler, -dar, -der, -zar, -zer, -sar, -ser, and so on. All these phonetic variations have not affected the semantics of this morphological feature of the quantity category, which is discussed in detail in the article.